-12x-x=12

Simple and best practice solution for -12x-x=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12x-x=12 equation:


Simplifying
-12x + -1x = 12

Combine like terms: -12x + -1x = -13x
-13x = 12

Solving
-13x = 12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '-13'.
x = -0.9230769231

Simplifying
x = -0.9230769231

See similar equations:

| 7m+2(1-m)-8m=-4 | | -2(x+4)=-30 | | 2h+1+h+4=h+16+h | | X-72=-9x | | 5g+2=3g+12 | | 6x+2y-5y+2x= | | 65=16-2n-5+8n | | 0=5m | | 2(f+2)+f=2f+7 | | -8x+6=-7x+3 | | 4m-2=24 | | 4x+-1=2(2x+-1) | | 5x+-10=4x+-2 | | 5x+-10=5x+-2 | | 4h-8h=2h | | 9e+24-2e=11e | | 15-0.8(z-2)=0.1(7z-2) | | 4=4(j+3) | | 6p+2(6-2p)= | | 10+130+40= | | -8x+6=-8x+3 | | -1(-1)=-3 | | 2(3d+1)=d+22 | | 10x-3-14x+8= | | -2x-130=-10x+110 | | 2y+2x=6y | | 3c+5=c+19 | | -2x+-3=-2x+-6 | | 0.3(21x-12)-(x+7)= | | 4b+2b=b+b+20 | | 4(1m-8)+8(1-8m)=-24 | | 10x+6=10x+3 |

Equations solver categories